2011
DOI: 10.1055/s-0031-1276803
|View full text |Cite
|
Sign up to set email alerts
|

Misteln in der Krebstherapie

Abstract: ■ Korrekturexemplar: Veröffentlichung (auch online), Vervielfältigung oder Weitergabe nicht erlaubt! ■ Daniela Umbreit ist Redakteurin der DMW.Ein Interessenkonflikt besteht nicht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…277 Umbreit et al found a very high rate of satisfied victims of the mediated cases in Texas and Ohio. 277 Umbreit et al found a very high rate of satisfied victims of the mediated cases in Texas and Ohio.…”
Section: Restorative Outcomesmentioning
confidence: 98%
See 3 more Smart Citations
“…277 Umbreit et al found a very high rate of satisfied victims of the mediated cases in Texas and Ohio. 277 Umbreit et al found a very high rate of satisfied victims of the mediated cases in Texas and Ohio.…”
Section: Restorative Outcomesmentioning
confidence: 98%
“…104 What is most notable about ongoing terrorist activity in comparison with one-time terrorist attacks in terms of PTSD prevalence is that those exposed to repeated and ongoing violence are at larger risk of developing PTSD. This is also the case for terrorism.…”
Section: One-off Versus Ongoing Terrorismmentioning
confidence: 99%
See 2 more Smart Citations